2013
DOI: 10.5603/cj.a2017.0077
|View full text |Cite
|
Sign up to set email alerts
|

Refined heart failure detection algorithm for improved clinical reliability of OptiVol alerts in CRT-D recipients

Abstract: (Cardiol J 2018; 25, 2: 236-244)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
0
20
2
Order By: Relevance
“…The story of RM using devices has progressed from singlephysiological parameter data to sophisticated combined algorithms. 10,18,19 Partners HF used multiple physiological parameters as part of a combined device-based diagnostic algorithm to identify patients at increased risk of heart events in the next 30 days. 10 However, despite promising results from subsequent retrospective analyses, the failure to demonstrate impact on hard outcomes as presented in REM-HF and MORE-CARE was disappointing and threatened to close the door on this avenue of care.…”
Section: Discussionmentioning
confidence: 99%
“…The story of RM using devices has progressed from singlephysiological parameter data to sophisticated combined algorithms. 10,18,19 Partners HF used multiple physiological parameters as part of a combined device-based diagnostic algorithm to identify patients at increased risk of heart events in the next 30 days. 10 However, despite promising results from subsequent retrospective analyses, the failure to demonstrate impact on hard outcomes as presented in REM-HF and MORE-CARE was disappointing and threatened to close the door on this avenue of care.…”
Section: Discussionmentioning
confidence: 99%
“…This method, used for the detection of cardiac decompensation, is considered to be a very sensitive but less specific tool, which leads to a high number of false positive alerts. We have previously described a refined device diagnostic algorithm based on parameters of low activity level, high nocturnal heart rate, and suboptimal biventricular pacing, which could significantly improve clinical reliability of OptiVol alerts [9]. However, a recent OptiLink heart failure study analyzing this technology failed to demonstrate any difference in the composite endpoint of all-cause mortality and cardiovascular hospitalization [29].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized studies proved that remote monitoring could reduce time to evaluate arrhythmic events [3], decrease mean length of cardiovascular hospitalizations [4], and could significantly lower the number of appropriate or inappropriate shocks [5]. This method is also able to reduce in-office implantable cardioverter defibrillator (ICD) follow-up burden safely [6] Remote monitoring also provided early detection of heart failure events and reduced the number of urgent in-office visits and total health care use in patients with ICD or cardiac resynchronization systems in diverse clinical studies [7-9].…”
Section: Introductionmentioning
confidence: 99%
“…Implantable devices to measure fluid status also exist, but such devices have yet to be evaluated in cardiorenal syndrome setting. One study showed the use of OptiVol (Medtronic), an intrathoracic impedance monitor, to improve heart failure prognosis, but had little effect on hospital admissions and outpatient visits despite utilization of visit alerts (Vamos et al, 2018). Pulmonary artery catheterization is no longer used clinically as it had demonstrated no benefit on mortality and rehospitalization in acute heart failure (Binanay et al, 2005), but it might be useful to detect and treat subclinical congestion (Rangaswami et al, 2019).…”
Section: Diagnosis Prognosis and Treatment Of Cardiorenal Syndromementioning
confidence: 99%